Legal Education And Social Justice - Faruqi, Shad Saleem (Journal of Malaysian and Comparative Law, 1979)
In Malaysia, as in most evolving democracies, a massive effort at social enginerring is underway. Law and legal institutions are being used not only to redefine relations, reorient expectations, redistribute wealth and opportunities, they are also being employed vigorously to control and dissipate the inevitable tensions and conflicts that result in any effort to bring about change or force the pace of change.